Pengetahuan dan Sikap Perempuan yang Sudah Menikah Terhadap Pencegahan Penularan Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) - Ayuningtias, Rayinda; Solehati, Tetti; Maryati, Ida (Universitas Aisyah Pringsewu, 2018)
The number of woman infected with HIV in Indonesia predicted to continue to rise. The main mode of this infection is through heterosexual and IDU this causes it to trigger the wide spread of infection to partner or wife.The purpose of this research was to find out the woman's knowledge and attitude toward the prevention of HIV/AIDS disease transmission at Kelurahan Kebon Pisang. This research was a quantitative research using descriptive method where study was conducted in September 2012 using questionnaires that were distributed to 350 respondents with stratified random sampling technique. The result of this research showed nearly to half of the respondents understood well about the object of transmission (44,9 percent), behavioral risk of contracting HIV (55,1 percent), and HIV prevention efforts (52 percent). In terms of attitude, nearly to half of respondents supported people with HIV/AIDS (52 percent) and HIV prevention efforts (58,6 percent). However, if viewed as averall attitude components 52,7 percent respondents have an attitude that did not support towards the prevention of HIV/AIDS. Therefore, the health care providers is expected to further optimize the programs that already exist related health promotion program on HIV/AIDS as whole to all society especially the womans.